P122 VATS can be used to effectively triage women with ovarian cancer and moderate to large pleural effusions to PDS or NACT/IDS. (1st November 2019) - Filippova, O; Bharathan, R; Cowan, R; Lakhman, Y; Tew, W; O'Cearbhaill, R; Konner, J; Park, B; Huang, J; Gardner, G; Sonoda, Y; Long Roche, K; et al.
Abstract : Introduction/Background: Malignant pleural effusion, denoting stage IV disease, is a commonly cited indication for neoadjuvant chemotherapy (NACT) in women with ovarian cancer. Our objective was to evaluate outcomes of women with moderate to large pleural effusions whose initial management, primary debulking surgery (PDS) vs. NACT, was determined according to our institutional video-assisted thoracic surgery (VATS) algorithm. Methodology: We conducted a retrospective review of patients with at least a pleural effusion who underwent VATS to guide management between 2001 and 2018. Data collected included VATS indication, findings, subsequent treatment and survival. Appropriate statistical analyses were applied. Results: 144 women underwent thoracic surgery; 32 were excluded because they had trans-diaphragmatic resection through the abdominal incision and 22 because of no pleural effusion on preoperative imaging or VATS was not performed as part of initial management. The study cohort included 90 women; median age was 59.5 years (range, 38–81). All VATS were performed by a thoracic surgeon; median operative time was 39 minutes (range, 12–100). 50 (56%) patients underwent PDS after VATS demonstrated either no intrathoracic tumor (n=25, 50%) or thoracic disease that was resected to ≤1cm (n=25, 50%). The outcomes of these 50 patients with subsequent abdominal PDS were: complete gross resection, 17 (34%); ≤1cm residual, 25 (50%); and >1cm residual, 8 (16%). In 40 patients (44%), VATS demonstrated chest disease that was not amenable to optimal resection. These patients were treated with NACT and interval debulking surgery (IDS). With a median follow-up time of 36 months, the 3-year survival rate was 79.2% for PDS and 54.4% for NACT/IDS. Median overall survival was 61.6 months and 39.1 months, respectively (p=0.024). Conclusion: In patients with ovarian cancer and moderate to large pleural effusions, optimal resection in both the chest and abdomen is possible with PDS. VATS can be used to effectively triage patients in this setting. Disclosure: Outside the submitted work, Dr. Chi reports personal fees from Bovie Medical Co., Verthermia Inc., C Surgeries, and Biom 'Up, as well as recent stock ownership from Intuitive Surgical, Inc. and TransEnterix, Inc.